2021
DOI: 10.1111/pan.14185
|View full text |Cite
|
Sign up to set email alerts
|

Differences in intubation outcomes for pediatric patients between pediatric and general Emergency Departments

Abstract: Background: Intubation is a life-saving intervention at the Emergency Department (ED). However, general and pediatric EDs may vary in their preparedness to manage children with airway emergencies. Aims:We aimed to compare rates of first-pass intubation and adverse tracheal intubation-associated events between general and pediatric EDs.Methods: A retrospective review of medical records was conducted at a pediatric ED and three general EDs from January 1, 2015, to December 31, 2018. Information about the intubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…The incidence of adverse events in pediatric EDs varies from 10% to 39%. 2 , 4 , 6 , 7 , 30 , 31 , 32 There were differences in median patient's age and level of intubator's training between the studies. Improving first‐attempt success rates is important because multiple attempts of intubation procedures increase adverse events.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The incidence of adverse events in pediatric EDs varies from 10% to 39%. 2 , 4 , 6 , 7 , 30 , 31 , 32 There were differences in median patient's age and level of intubator's training between the studies. Improving first‐attempt success rates is important because multiple attempts of intubation procedures increase adverse events.…”
Section: Discussionmentioning
confidence: 88%
“…However, EDs have different characteristics from those settings, such as limited medical resources and time, so ED‐specific knowledge is required. 6 , 7 Recently, a large registry of general (i.e., nonpediatric) ED settings has revealed pediatric findings—variations in the intubation success rate by patient's age and provider training level. 6 , 8 , 9 , 10 , 11 Successful first‐attempt intubation is important because studies have shown that repeated intubations are associated with a higher rate of complications.…”
Section: Introductionmentioning
confidence: 99%
“…The observed frequency of tracheal tube misplacement of 26.0% and particularly 12.3% endobronchial intubation in our study is in line with the results of previous pediatric studies. In the last two decades, various frequencies of endobronchial tube misplacements, ranging from 0% [ 8 ], over 2.4% [ 3 ], 3.6% [ 14 ], 6.2% [ 19 ], 6.4% [ 18 ], 8% [ 17 ] 12.8% [ 16 ], 13.2% [ 21 ], to 21.0%, have been reported [ 12 ]. Furthermore, some studies assessing pediatric tube positions found that the tube tips were generally placed too deep in even larger proportions (24.5% [ 16 ], 38.3% [ 20 ], 38.9% [ 15 ], 50.0% [ 12 ], and 69% [ 24 ], respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unrecognized endobronchial intubation may also lead to avoidable chest tube placement at the unventilated chest side due to absent breath sounds mimicking pneumothorax [ 11 , 12 ]. Although there is previous evidence that children are prone to endobronchial intubation, studies identifying associated factors are scarce [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accidental one-lung intubation occurs in about 5% of adult patients in intensive care, 28% of those with cardiac arrest and 10% of those with out-of-hospital endotracheal intubations (Dronen et al 1982;Brunel et al 1989;Timmermann et al 2007). By contrast, pediatric data demonstrate that inadvertent placement of the endotracheal tube into the bronchus during intubation is a fairly common occurrence: up to 18.9% of intubation in pediatric emergency departments and 15.4% of intubations in pediatric intensive care units result in mainstem intubation (Kerrey et al 2009;Nishisaki et al 2013; Alonso Quintela et al 2014;Mori et al 2019;To et al 2021). Our results show that the use of lung ultrasound to detect tracheal and mainstem intubation as an initial strategy in critically ill pediatric patients is associated with high accuracy.…”
Section: Discussionmentioning
confidence: 99%